EFFECT OF GRAPHENE ON THE MECHANICAL AND ELECTROCHEMICAL PROPERTIES OF GLARE - Wang, Shuo; Cong, Fanglin; Araby, Sherif; Kaytbay, Saleh; Cai, Rui; Cui, Xu; Meng, Qingshi (Journal of Adhesion Science and Technology, 2021)
This study explores the effect of different graphene contents on the mechanical behaviour, tensile and flexural properties, and the electrochemical performance of cross-layered glass-reinforced aluminium (GLARE) laminates. Results show that the mechanical properties of GLARE with different graphene contents are similar but not identical. The mass fraction of graphene (0 wt.%–1.0 wt.%) is calculated from the total mass of adhesive. As the graphene content increases (0 wt.%–1.0 wt.%), flexural strength peaks in the presence of 0.5 wt.% graphene, but tensile strength continues to increase. When the graphene mass ratio is 1.0 wt.%, the maximum tensile strength is 245.45 MPa. When the graphene mass ratio is 0.5 wt.%, interlaminar shear strength and flexural strength are 19.06 and 260.22 MPa, respectively, which correspond to different span–thickness ratios of 8/1 and 32/1. This graphene mass ratio indicates the best three-point flexural performance of graphene-reinforced GLARE. This study further explains the enhancement mechanism through fracture surface observation. Graphene with a mass ratio of 0.5 wt.% maximises the flexural strength whilst maintaining a strong GLARE electrochemical performance. At scanning speeds of 40, 80, and 100 mV/s, the specific capacitance values are 1.76, 2.47, and 2.88 F/g, respectively. According to quantum tunnelling theory, graphene can form a conductive network when it is dispersed in a resin matrix. This theory reveals the reason why 0.5 wt.% graphene platelet-modified GLARE has good electrochemical properties.
Keywords: Type of access: Open Access; GLARE; mechanical properties; electrochemical performance; graphene